Multi-Stage Hydraulic Fracturing Completion Design Based on Ball-and-Sleeve Method - Kasi, Njeudjang; Zanga, Alain Amougou; Ndougsa-Mbarga, Théophile; Njandjock Nouck, Philippe (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
This paper proposes a completion that can allow fracturing four zones in a single trip in the well called “Y” (for confidential reasons) of the field named “X” (for confidential reasons). The steps to design a well completion for multiple fracturing are first to select the best completion method then the required equipment and the materials that it is made of. After that, the completion schematic must be drawn by using Power Draw in this case, and the summary installation procedures explained. The data used to design the completion are the well trajectory, the reservoir data (including temperature, pressure and fluid properties), the production and injection strategy. The results suggest that multi-stage hydraulic fracturing can be done in a single trip by using the ball-and-sleeve method. Metallurgy and hydrogenated nitrile are sealing elementary constituent of chromium which are essential materials found in alloy with 13% of chromium.